2019
DOI: 10.1128/jvi.01194-19
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Latent HIV-1 T Cell Reservoirs with a Combination of Innate Immune and Epigenetic Regulators

Abstract: The presence of T cell reservoirs in which human immunodeficiency virus (HIV) establishes latency by integrating into the host genome represents a major obstacle to an HIV cure and has prompted the development of strategies aimed at the eradication of HIV from latently infected cells. The “shock-and-kill” strategy is one of the most pursued approaches to the elimination of viral reservoirs. Although several latency-reversing agents (LRAs) have shown promising reactivation activity, they have failed to eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…A defective STING pathway may render human T cells vulnerable to other pathogens, due to low production of IFN, including other retroviruses (e.g., human T-lymphotropic virus type 1), or viruses (e.g., VZV and HHV 6) that replicate through a DNA ( 18 ). Conversely, other downstream signaling of STING than IFN, like NFκB, are less affected in human T cells, as shown in HIV-1 lymphocytes ( 38 ). This is also observed in SAVI syndromes (induced by gain of function of STING), where over-activation of STING by viruses can lead to T cell hyper-responsiveness with IL-6 secretion (as well as T cell exhaustion, and autophagy-induced lymphopenia).…”
Section: Introductionmentioning
confidence: 99%
“…A defective STING pathway may render human T cells vulnerable to other pathogens, due to low production of IFN, including other retroviruses (e.g., human T-lymphotropic virus type 1), or viruses (e.g., VZV and HHV 6) that replicate through a DNA ( 18 ). Conversely, other downstream signaling of STING than IFN, like NFκB, are less affected in human T cells, as shown in HIV-1 lymphocytes ( 38 ). This is also observed in SAVI syndromes (induced by gain of function of STING), where over-activation of STING by viruses can lead to T cell hyper-responsiveness with IL-6 secretion (as well as T cell exhaustion, and autophagy-induced lymphopenia).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, any treatment interruption or drug-resistant mutations acquired by the virus can lead to rapid viral rebound. Several LRAs have been employed in an attempt to reactivate latent viruses and clear the viral reservoirs [3,43]. In a recent report, both for in vitro and in ex vivo patient samples, a combination of activators of HIV-1 specific innate immune response and epigenetic modulators has been shown to be effective in latency reversal and targeted killing of HIV-infected T cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…Several LRAs have been employed in an attempt to reactivate latent viruses and clear the viral reservoirs [3,43]. In a recent report, both for in vitro and in ex vivo patient samples, a combination of activators of HIV-1 specific innate immune response and epigenetic modulators has been shown to be effective in latency reversal and targeted killing of HIV-infected T cells [43]. Furthermore, an ex vivo study demonstrated the elimination of recrudesced HIV-1 latently infected cells treated with a combination of nnAb along with nAbs of diverse epitope specificities, implicating that administration of a combination of mAbs with distinct epitope specificities should be considered in strategies to clear latent HIV-1 infection in vivo [44].…”
Section: Discussionmentioning
confidence: 99%
“…The type-I IFNs are the principal first line of defense against viral infections, and failure to mount an effective IFN response leads to widespread systemic infection in the host ( Huang et al, 2019 ). With respect to the human immunodeficiency virus (HIV), innate immunity is of paramount importance to control HIV-1 infection as it is the principal way not only to prevent widespread establishment of latent reservoirs, but also to deplete them ( Soper et al, 2017 ; Palermo et al, 2019 ). The success of other strategies to eliminate latent reservoirs for a functional cure could be enhanced if the innate immunity against HIV-1 is strengthened ( Altfeld and Gale, 2015 ).…”
Section: Introductionmentioning
confidence: 99%